A Rare Case of Orthograde Retrieval of Extruded Instrument following Periapical Tissue Healing - Ahmed Elhakim; Tarek Mohamed Abd El-Wahab (Case Reports in Dentistry)
The ideal retrieval protocol of separated instruments reverts the case to the initial situation prior to the fracture incidence while preserving the tooth hard tissue and the integrity of the supporting structures. When a patient presented for emergency treatment of tooth #37 diagnosed with acute suppurative apical periodontitis, radiographic examination revealed a fractured instrument extruded into the periapex. The treatment options for retrieval were limited to replantation. The initial emergency treatment which consisted of orthograde pus drain, radicular disinfection, and intracanal calcium hydroxide dressing completely resolved patient’s symptoms. The follow-up radiographs revealed an interesting finding: gradual shift in the separated fragment position into the radicular space allowing a successful nonsurgical removal of the broken instrument. In conclusion, the reaction of periodontal tissues to an extruded instrument fragment remaining in situ may be favourable; thus, a risk and benefit analysis approach is essential to fractured instrument retrieval.